Learning Methods in the Modern Era Perspectives of Muhammad Obaidat and Hamadna - Mutamimah, Duwi Habsari; Basuki, Basuki; Ahmad, Abdul Kadir (Tarbawi: Journal of Islamic Education, 2024)
This article aims to discover the modern era's learning methods according to Muhammad Obaidat and Hamadna. This research method uses library research, there are two sources of data in this study, first primary and secondary sources. Data analysis in this study used analysis content. This research refers to the book: Mafaahimu Tadriisi Fii Ngasri Al-Hadiisi as a primary source, the author chose the book because it discusses learning methods in the modern era. As for secondary sources, the author uses related journals and books. This research resulted in 6 points that there are learning methods in Education that can be used in learning in the modern era, namely project methods, assignment methods, field visit methods, survey methods, conceptual maps, and play while learning methods. This method contributes positively to student learning and improves the quality of educators in teaching, besides that educators and students interact with each other with learning content more dynamically and effectively.